The Effect of the Zimmermann Model on the Perceived Self-Efficacy of the Fifth Scientific Students - et.al, Abdul-Rahim Abdul-Karim Kazem Al-Tamimi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the current research is to find out the effect of the Zimmermann model of the fifth scientific students on their perceived self-efficacy, and for the purpose of verifying the goal of the research, the researcher puts the following null hypothesis. There is no statistically significant difference at the level of significance (0.05) between the mean scores of the experimental group students who study according to the Zimmermann model and the control group students who study according to the usual method in the scale of perceived self-efficacy they have. In order to verify the validity of this hypothesis, the two researchers conducted an experiment that lasted a whole semester for the academic year (2020-2021), where the researchers approved the experimental design of two groups, one experimental and the other with partial control and the post-test of the scale of perceived self-efficacy. The research was limited within its limits to fifth-grade scientific students at Salah al-Din al-Ayyubi School for Boys affiliated to the General Directorate of Education in Baghdad, Rusafa al-Aula, for the academic year (2020-2021 AD). When the research sample reached (63) students, and Division (A) was the experimental group consisting of (32) students and Division (B) was the control group consisting of (31) students, the two research groups were rewarded with a number of the following variables (chronological age in months, achievement Last year, previous information, a measure of perceived self-efficacy), the research tool was prepared, which is a measure of perceived self-efficacy, which consisted of (30) items, and the validity of the tool was verified after it was presented to the arbitrators, and the data was analyzed and processed statistically by adopting the statistical program (spss). The results showed that the experimental group students who studied according to the Zimmermann model outperformed the control group students who studied according to the usual method in the perceived self-efficacy scale. Based on the results of the research, the researcher recommended the necessity of adopting the Zimmermann model in teaching biology for the scientific fifth grade because it has a positive effect on the perceived self-efficacy of students.